Wyrażenie persona grata ‛osoba mile widziana, pożądana’ w językach słowiańskich na tle wyrażenia persona non grata ‛osoba niemile widziana, niepożądana’ - Lewaszkiewicz, Tadeusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The expressions persona grata and persona non grata (the latter evidenced mainly in its diplomatic meaning) are undoubtedly current in all Slavic languages, although for some of them they are not found in lexicographic sources used in the article. In the majority of Slavic languages, the expression persona non grata seems to occur more often than persona grata, a fact that can be gleaned from national corpora of Slavic language which the author managed to access for the purposes of this article. The fact that in the Russian language corpus the expression persona non grata only slightly prevails over persona grata, while in the Upper Sorbian language corpus there are more examples of persona grata than persona non grata, is particularly noteworthy.